Beyond performance: Emotions before and after semi-high-stakes mathematics testing among school-aged students - Kyynäräinen, Reetta; Holopainen, Santeri; Metsämuuronen, Jari; Bin Qushem, Umar; Laakso, Mikko-Jussi; Alanko, Katarina (John Wiley & Sons, 2026)
Background
Previous research has shown that testing differs significantly from other classroom activities and is associated with heightened negative emotions and lower levels of positive emotions. However, relatively little is known about students' emotions surrounding testing, particularly in higher-stakes assessment settings.
Aims
This study aims to examine how students' levels of four emotions (i.e., happiness, relaxation, anxiety and boredom) develop from pre to-post-test, and it investigates how individual factors (i.e., gender, grade level, perceived mathematical competence and test performance), impact students' emotional states and moderate their emotional trajectories.
Sample
The sample (N = 2179) consists of 692 third-grade, 605 sixth-grade, 413 eighth-grade and 469 ninth-grade students from various schools across Finland, who participated in a digital, semi-high-stakes, end-of-year mathematics assessment.
Methods
An in-situ approach was used to assess students' emotions immediately before and after testing. Analyses were conducted using linear mixed-effects modelling to account for the repeated-measurements structure.
Results and Conclusions
Students generally reported lower positive emotions after the assessment. The measured individual factors significantly predict both students' emotional states and their development during the assessment. Boys reported higher levels of positive emotions and lower anxiety, while younger students remained more positive during the assessment. Students who perceived themselves as competent experienced higher levels of positive and lower levels of negative emotions, whereas students who performed poorly showed a decline in positive emotions during the assessment. Future research could focus on whether support for emotional regulation affects student performance in test situations.